Forecasting – Informative Properties Of Natural Complexes Delta Exit Geosystems (Eurasian Journal of History, Geography and Economics, 2024)
This article highlights the issues of predictive and informative properties of natural complexes of desert landscapes on the example of the deltaic geosystems of Uzbekistan